2005
DOI: 10.1074/jbc.m501674200
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Exocyst Complex Is Required for the Docking Step of InsulinVesicle Exocytosis

Abstract: Glucose stimulates insulin secretion from pancreatic ␤ cells by inducing the recruitment and fusion of insulin vesicles to the plasma membrane. However, little is currently known about the mechanism of the initial docking or tethering of insulin vesicles prior to fusion. Here, we examined the role of the SEC6-SEC8 (exocyst) complex, implicated in trafficking of secretory vesicles to fusion sites in the plasma membrane in yeast and in regulating glucose-stimulated insulin secretion from pancreatic MIN6 ␤ cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 42 publications
(55 reference statements)
8
71
0
Order By: Relevance
“…However, the incorporation of VSV-G into the PM was significantly affected, as revealed by the 8G5 antibody specifically recognizing the extracellular domain of VSV-G. Similarly the exocyst has been implicated in tethering and fusion of Glut4-containing vesicles in 3T3-L1 adipocytes (Inoue et al, 2003;Ewart et al, 2005;Tsuboi et al, 2005). It is possible that other exocyst components also interact with phospholipids (Moskalenko et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, the incorporation of VSV-G into the PM was significantly affected, as revealed by the 8G5 antibody specifically recognizing the extracellular domain of VSV-G. Similarly the exocyst has been implicated in tethering and fusion of Glut4-containing vesicles in 3T3-L1 adipocytes (Inoue et al, 2003;Ewart et al, 2005;Tsuboi et al, 2005). It is possible that other exocyst components also interact with phospholipids (Moskalenko et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…32 Therefore, we hypothesized that TNFAIP2 could promote angiogenesis by upregulating VEGF secretion. However, we did not observe any decrease in VEGF secretion by TNFAIP2-knockdown HK1 cells (Figure 3d), suggesting that TNFAIP2 is not involved in the regulation of VEGF secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we tested for a potential interaction between TNFAIP2 and VEGF, an important secreted angiogenesis-initiating factor that has also been correlated with microvessel density in nasopharyngeal carcinoma patients. 30 As the protein sequence of TNFAIP2 (amino acids 91-651) is highly similar to that of SEC6 (based on a publicly available website http://www.sanger.ac.uk/), an exocyst complex component involved in exocytosis 31 and secretion, 32 we examined whether TNFAIP2 affected the secretion of VEGF by HK1 cells. As shown in Figure 3d, our results revealed that VEGF secretion by HK1 cells was not affected by TNFAIP2 knockdown.…”
Section: Promotion Of Cell Migration and Invasion By Tnfaip2mentioning
confidence: 99%
“…Among its proposed roles, the exocyst is thought to function as a vesicle tether at the plasma membrane and contribute to the specificity of membrane fusion (5). Recent studies in the ␤-cell demonstrated that the exocyst regulates the ability of insulin granules to dock with the plasma membrane (10).…”
Section: Snaresmentioning
confidence: 99%
“…Exo70 Interacts with a Helical Domain in the C Terminus of Snapin-Snapin contains an N-terminal hydrophobic domain (amino acids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and two helical domains (amino acids 37-65 and 83-119), the second of which is the major binding site for SNAP23 (22). To map the Exo70 binding domain in Snapin, a series of FLAG-Snapin truncation mutants were generated ( Fig.…”
Section: Identification Of Snapin As An Exo70-binding Protein-mentioning
confidence: 99%